Answer:
D: -5(-6x^2 + x + 2)
E: 5(2x + 1)(3x − 2)
Step-by-step explanation:
The <em>first two answer choices have incorrect constants</em> (25 and 3 vs -10). A factor of 5 is removed from the remaining answer choices, so let's remove a factor of 5 and see what we get:
30x^2 -5x -10 = 5(6x^2 -x -2)
An additional x cannot be factored from the expression, so <em>choice C can be eliminated</em>.
Multiplying each of these factors by -1 will make the product correspond to answer choice D.
Factoring will make it correspond to answer choice E, best verified by finding the x-term of the product of the binomial factors:
E: 2x(-2) +1(3x) = -x, as required
F: 2x(2) -1(3x) = x, wrong sign
The equivalent expressions are those of choices D and E.
Answer:
8
Step-by-step explanation:
A=l*w
32*2=64
A=s*s
s=√A
√64
=8
(x+2)(1-x)=-4
subtract 2 from both sides: x(1-x)=2
simplify:x-2x=2
subtract: -x=2
switch the negatives
x=-2
12/10 = 1 2/10 or 1 1/5
15/6 = 2 3/6 or 2 1/2.
To turn these fractions into mixed numbers you have to see how much times the denominator can go into the numerator and the amount of numbers left over. For 12/10, 10 can go into 12 1 time, so the whole number is 1. There is 2 numbers left over, so the numerator is 2 and you do not have to change the denominator. To simplify, divide the numerator and denominator by the highest number it can be divided to